Fosfomycin Trometamol Is Noninferior to Trimethoprim–Sulfamethoxazole for Acute Uncomplicated Cystitis in Women. (4th October 2017) - Stapleton, Ann; Roberts, Pacita; Cox, Marsha; Hooton, Thomas
Abstract: Background: Acute uncomplicated cystitis (AUC) is an exceedingly common infection among young women. Although fosfomycin trometamol (FT) is listed as a first-line agent for AUC per the 2011 IDSA Guidelines, data on the efficacy of FT in AUC submitted to FDA for this agent were decades old and indicated inferior efficacy (81% cure rate) compared with standard short-course regimens. Thus, we conducted a study of single-dose FT compared with 3-day therapy with another key first-line agent, trimethoprim-sulfamethoxazole (TMP-SMX), in young women with AUC to assess noninferiority of FT to TMP-SMX, allowing for a noninferiority margin of 10%. Methods: 297 healthy women with AUC, ages 18 to 45, were randomized to treatment with FT 3g single dose given as a sachet or TMP-SMX DS tablet twice daily for 3 days and followed prospectively for one month. Urinalysis and urine culture were performed at baseline and at follow-up visits at 5 to 9 and 28 to 30 days after completion of therapy. Cure was defined as no further treatment for subsequent or unresolved symptoms. Results: 296 subjects were evaluable at the end of the study. The cure rate for FT was 86.7% (130/150) vs. 82.2% (120/146) for TMP-SMX ( P = 0.0003 for noninferiority). For E. coli, the causative pathogen in 76% of cases, resistance (resistant or intermediate susceptibility) to the treating antimicrobial occurred in 0% of FT subjects and 20% of TMP-SMX subjects. Conclusion: Fosfomycin trometamol is non-inferior to TMP-SMX for treatment of AUC in healthy young women. Cure rates for FT (86.7%) are comparable to those of TMP-SMX (82.2%) and no E. coli resistance to FT was seen, as compared with a 20% rate for TMP-SMX. These data support the use of FT for treatment of AUC among healthy young women. Disclosures: All authors: No reported disclosures.